A review of struvite crystallization for nutrient source recovery from wastewater - Guan, Qian; Li, Yingpeng; Zhong, Yun; Liu, Wei; Zhang, Jiajie; Yu, Xin; Ou, Ranwen; Zeng, Guisheng (Journal of environmental management, 2023)
Nutrient recovery from wastewater not only reduces the nutrient load on water resources but also alleviates the environmental problems in aquatic ecosystems, which is a solution to achieve a sustainable society. Besides, struvite crystallization technology is considered a potential nutrient recovery technology because the precipitate obtained can be reused as a slow-release fertilizer. This review presents the basic properties of struvite and the theory of the basic crystallization process. In addition, the possible influencing variables of the struvite crystallization process on the recovery efficiency and product purity are also examined in detail. Then, the advanced auxiliary technologies for facilitating the struvite crystallization process are systematically discussed. Moreover, the economic and environmental benefits of the struvite crystallization process for nutrient recovery are introduced. Finally, the shortcomings and inadequacies of struvite crystallization technology are presented, and future research prospects are provided. This work serves as the foundation for the future use of struvite crystallization technology to recover nutrients in response to the increasingly serious environmental problems and resource depletion. [Display omitted] •Struvite crystallization processes for nutrient recovery from wastewater are overviewed.•Assessment of performance of novel technologies assisted with struvite crystallization process.•Analysis of economic feasibility and environmental impacts in struvite recovery process.•Current challenges and future prospects directions are identified.